Does it matter how I stream? Comparative analysis of livestreaming marketing formats on Amazon Live - Isaac Owusu Asante; Yushi Jiang; Xiao Luo (Humanities & Social Sciences Communications, 2023)
Abstract Livestreaming commerce has become a shopping option following the outbreak of COVID-19, and many sellers have adopted livestreaming marketing to increase their sales and market share. Although livestreaming marketing offers many opportunities, sellers face the challenge of identifying an effective product demonstration format to attract more viewers and increase engagement behaviors during livestreaming sessions. Based on social capital and signaling theories, this study evaluates the relationships among social capital acquisition, social endorsement, and consumer engagement constructs across three different livestreaming marketing product demonstration formats. Partial least squares structural equation modeling (PLS-SEM) multivariate analysis shows that social capital acquisition and endorsement positively affect consumer engagement across all livestreaming formats. A cross-case assessment based on Henseler’s bootstrap-based multigroup analysis reveals that although the preference for the interview livestreaming marketing format is lower, it is more efficient in attracting consumer engagement than the tutorial and behind-the-scenes livestreaming marketing formats. This study is thus the first in the scientific literature to examine consumer engagement’s antecedents across different livestreaming marketing formats.